US consumer perception survey of animal welfare in broiler stunning - Barahona-Dominguez, Linda; An, Jihye; Baker-Cook, Bethany; Cho, Sungeun (Frontiers in Animal Science, 2025)
From a poultry welfare perspective, stunning methods used in processing are among the most debated topics within the industry. There are two commercial stunning methods: electrical and controlled atmosphere stunning. However, it has yet to be determined whether one is superior to the other. An online survey was conducted to assess consumer perception of stunning and animal welfare. A total of 986 responses were collected from regular American chicken meat consumers. The objective knowledge assessment showed that 10% of respondents knew what stunning is, while 22% had a conceptual understanding of animal welfare. Consumers still prioritize food safety and pricing over animal welfare–enhanced products. When participants were segmented according to their knowledge of poultry processing, 18% of consumers were considered “high knowledge.” This study contributes to a better understanding of consumer perception of poultry welfare, which may help guide industry practices.